Governance of Public Pension Funds : Lessons from Corporate Governance and International Evidence - Hess, David; Impavido, Gregorio (World Bank, Washington, DC, 2014)
An understanding of corporate governance theory can promote the adoption of appropriate governance tools to limit agency problems in public pension fund management. The absence of a market for corporate control hinders the translation of lessons from the private sector corporate world to public pension governance. The establishment of a fit, and proper governing body for public pension funds, thus may be even more important than the maintenance of a comparable body for private sector corporations. In particular, behavioral controls should be carefully designed.